2022
DOI: 10.1101/2022.06.29.496888
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-nuclei Transcriptome of Human AT Reveals Metabolically Distinct Depot-Specific Adipose Progenitor Subpopulations

Abstract: Single-cell and single-nuclei RNA sequencing data (scRNAseq and snRNAseq, respectively) have revealed substantial heterogeneity in the AT (AT) cellular landscape in rodents and humans depending on depot and disease status. We used snRNAseq to characterize the cellular landscape of human visceral (VAT) and subcutaneous AT (SAT) samples from lean subjects and subjects with obesity. We identified multiple cell types in the AT cellular repertoire, including three major AT stromal cell (ASC) subpopulations, multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 65 publications
(130 reference statements)
4
9
1
Order By: Relevance
“…SAT-specific MAC3 was majorly characterized by Frontiers in Cell and Developmental Biology frontiersin.org ABL1, which's expression regulates macrophage podosome formation, SPTBN1, ZBTB16, and ADAMTSL3. In agreement with previous studies in human AT (Jaitin et al, 2019;Vijay et al, 2020;Strieder-Barboza et al, 2022), MAC4 had a lipid associated macrophage (LAM) profile with high expression of FABP4, LPL, CD36, FASN, CD9, among other lipid related genes (Figure 6D, Supplementary Table S10). Abundance of MAC4 nuclei was increased by approximately 2-fold in VAT compared to SAT (20.3% vs. 10.6%) and SAT MAC4 had increased expression of lipogenic genes (FASN, SCD, and ACLY) when compared to VAT MAC4 (Supplementary Table S12).…”
Section: Macrophages Are the Predominant Immune Cell Type In Vat And ...supporting
confidence: 91%
See 4 more Smart Citations
“…SAT-specific MAC3 was majorly characterized by Frontiers in Cell and Developmental Biology frontiersin.org ABL1, which's expression regulates macrophage podosome formation, SPTBN1, ZBTB16, and ADAMTSL3. In agreement with previous studies in human AT (Jaitin et al, 2019;Vijay et al, 2020;Strieder-Barboza et al, 2022), MAC4 had a lipid associated macrophage (LAM) profile with high expression of FABP4, LPL, CD36, FASN, CD9, among other lipid related genes (Figure 6D, Supplementary Table S10). Abundance of MAC4 nuclei was increased by approximately 2-fold in VAT compared to SAT (20.3% vs. 10.6%) and SAT MAC4 had increased expression of lipogenic genes (FASN, SCD, and ACLY) when compared to VAT MAC4 (Supplementary Table S12).…”
Section: Macrophages Are the Predominant Immune Cell Type In Vat And ...supporting
confidence: 91%
“…We have summarized the gene profile of each cell type and subtype in VAT and SAT of dairy cows revealed by our study in Graphical abstract. Part of the different cell types and depot-specificities characterized in the present study have been previously reported in mice and human models (e.g., Vijay et al, 2020;Emont et al, 2022;Strieder-Barboza et al, 2022). Compared with human AT single-cell databases, we observed that AT from dairy cows is as diverse as human SAT and VAT with similar cell types and subtypes, including numerous ASPCs, EC, and immune cells, and VATspecific ME.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations